Scheduling Algorithms in Cloud Environments: A Comparative Study - A Murali, Juliet; Brindha, T (International Journal of Engineering and Technology, 2019)
Cloud is a distributed environment, having large capacity data centers. It needs parallel processing and task scheduling. Map Reduce is the programming model for processing this big data. Hadoop is a Java-based open source implementation of the Map-Reduce framework. The task scheduling in the MapReduce framework is an optimization problem. This paper describes some advantages, disadvantages, approaches used and the performance metrics comparison of different cloud scheduling algorithms and Hadoop Map Reduce scheduling algorithms.